Efficacy of Pulmonary Vein Isolation on Left Atrial Function in Paroxysmal and Persistent Atrial Fibrillation and the Dependency on Its Baseline Function. Issue 7 (6th March 2013) - Yoshida, Naoyasu; Okamoto, Mitsunori; Hirao, Hidekazu; Suenari, Kazuyoshi; Nanba, Kiyomi; Kinoshita, Hiroki; Matsumura, Masaya; Uchida, Mio; Kinoshita, Mirai; Watari, Yuichiro; Fukuda, Yukihiro; Ueda, Hironori
<x xml:space="preserve">Abstract</x> Background The effects of pulmonary vein (PV) isolation in atrial fibrillation (AF) on left atrial (LA) function or PV flow have not been well documented. Methods We examined the LA function and PV flow before and 3–6 months after PV isolation in 67 AF patients (34 paroxysmal [PAF] and 33 persistent [CAF]) using transesophageal echocardiography. Results AF recurred in 6/34 patients with PAF and in 6/33 patients with CAF 6 months after PV isolation. A larger LA dimension, a lower systolic PV flow velocity, and a lower ratio of systolic to diastolic PV flow velocity were related to a higher incidence of AF recurrence. The increment of left atrial appendage (LAA) flow velocity (55% vs. 22%) and systolic PV flow velocity (57% vs. 20%) after PV isolation tended to be greater in CAF than in PAF. The changes in LAA flow velocity had reverse correlations with the baseline values before PV isolation (PAF: r = −0.73, CAF: r = −0.58). The changes in mitral flow velocity during atrial contraction in PAF had reverse correlations with the baseline values before PV isolation (r = −0.84). The changes in systolic and diastolic PV flow velocity of PAF had reverse correlations with the baseline values before PV isolation (r = −0.56, r = −0.66). Conclusion The baseline LA function may affect AF recurrence as well as the improvement of LA function, and the benefit of successful PV isolation might be greater in CAF than in PAF.